Társadalmi konfliktusokat generáló ökológiai történések a Balaton életében az utóbbi néhány évtizedben – A víz zöld elszíneződése, az eutrofizáció - Pálffy, Károly (Acta Scientiarum Socialium, 2013)
Social Conflict Generating Ecological Developments in the Life of Lake Balaton in Recent Decades – Eutrophication, the green discolouration of the water As a result of increased nutrient loads affecting Lake Balaton phytoplankton biomass showed a considerable rise from the 1970s onwards, particularly in summer, indicating eutrophication, a process eventually leading to unfavourable ecological conditions. Summer blooms were increasingly dominated by filamentous N2-fixing cyanobacteria, particularly in the western basin showing a shift from eutrophic to hypertrophic state. Increased phosphorus loading was found to be the major cause of eutrophication in the lake, thus, in order to eliminate the sources of excessive nutrient input and its harmful consequences the 1980s saw the elaboration of reasoned restoration efforts including the adoption of phosphorus removal in wastewater treatment, sewage water diversion and the establishment of the Kis-Balaton reservoir. Due to these technical solutions eutrophication has been reversed, the trophic state of the lake has been showing a decreasing trend since 1995.